Exploring desert stone: John N. Macomb's 1859 expedition to the canyonlands of the Colorado - Madsen, Steven K., author; Utah State University Press, publisher (Colorado State University. Libraries, 2010)
The confluence of the Green and Colorado Rivers, now in Canyonlands National Park, near popular tourist destination Moab, still cannot be reached or viewed easily. Much of the surrounding region remained remote and rarely visited for decades after settlement of other parts of the West. The first U.S. government expedition to explore the canyon country and the Four Corners area was led by John Macomb of the army's topographical engineers. The soldiers and scientists followed in part the Old Spanish Trail, whose location they documented and verified. Seeking to find the confluence of the Colorado.
The story of the Macomb San Juan exploring expedition -- Organizing the expedition -- The expedition -- The expedition's aftermath -- The bones and the map -- Epilogue -- Selected documents of th San Juan exploring expedition -- The camps of the San Juan exploring expedition -- Diary of Charles H. Dimmock -- Topographical memoir of Charles H. Dimmock -- Abridged diary of John S. Newberry -- 1859 letters of John N. Macomb, Jr., to his wife -- Letters of John S. Newberry to Spencer F. Baird -- Letters of Frederick W. von Egloffstein to John N. Macomb, Jr.
Keywords: Geological surveys -- Four Corners Region -- History -- 19th century; Geological surveys -- Four Corners Region -- History -- 19th century -- Sources; Scientific expeditions -- Four Corners Region -- History -- 19th century; Canyons -- Four Corners Region -- History -- 19th century; Paleontology -- Four Corners Region -- History -- 19th century; Four Corners Region -- Geography; Four Corners Region -- Discovery and exploration; Colorado River (Colo.-Mexico) -- Discovery and exploration; Macomb, J. N. (John N.), 1810 or 1811-1889 -- Travel -- Four Corners Region; United States. Army. Corps of Topographical Engineers